Employment policies, hiring practices and firm performance - Sylvie Blasco; Barbara Pertold-Gebicka (Institute for the Study of Labor (IZA), 2012)
In this paper we investigate how active labour market policy programmes affect firms' hiring strategies and, eventually, firms' performance. We focus on counseling and monitoring which may reduce search costs for employers, but which may have ambiguous effect on the employer-employee matching quality and thus on firms' performance. Using a large scale experiment which was conducted in Denmark in 2005-2006 and induced a greater provision of activation, we find that small firms hiring in the districts where the social experiment was conducted changed their hiring practices in favor of unemployed workers and experienced greater turnover than the other firms. Treated firms also experienced no change or a marginal reduction in value added and total factor productivity during the first years after the experiment. These results are consistent with the idea that monitoring creates compulsion effects which counteract the possible improvement in the matching process expected from job search assistance.
Keywords: C21; J63; J68; 330; active labour market programmes; counseling and monitoring; hiring decisions; firms performance